Gain-aware caching scheme for information-centric networking - Long CHEN; Hong-bo TANG; Xing-guo LUO; Yi BAI; Zhen ZHANG (Tongxin xuebao)
The in-network caching system of information-centric networking had to deal with the popularity of huge number of content chunks and make efficient usage of storage resources.A content popularity based caching gain opti-mization model aimed to get maximum reduction of content retrieve cost was established,and a gain-aware caching scheme was proposed.By utilizing filtering effect of cache to request flow is scheme achieves caching cooperation and diversity potentially while maximizing caching gain of every single node.Bloom filter based sliding window strategy captures the content chunks with high caching gain according to request arrival interval and retrieval cost from the source.Analysis shows that the method can drastically reduce memory consumption caused by popularity monitoring.The simu-lation results illuminate that this scheme is well aware of content popularity based caching gain,and gets better band-width saving and cache hit ratio when content popularity is changing dynamically.